Far‐Right Illiberalism in the European Parliament - Larissa Böckmann; Sarah L. de Lange; Nathalie Brack; Matthijs Rooduijn (Politics and Governance)
The rise of illiberalism has become a global concern, especially since the establishment of far‐right illiberal regimes in countries such as Hungary, India, Poland, and Turkey. When in power, far‐right parties tend to promote democratic backsliding, leading to a proliferation of studies of the illiberal regimes established by the far‐right. Less attention has been paid so far to the embrace of illiberal ideas by these parties. Although studies of these parties’ populism, nativism, and authoritarianism are ubiquitous, we know little about the way in which these three ideological pillars become integrated into an overarching illiberal agenda. This article aims to analyze the extent to which European far‐right parties embrace illiberal ideas, irrespective of whether they are in power. To pursue this objective, we focus on parliamentary speeches given by far‐right parties in the European Parliament between 1999 and 2019. Methodologically, we employ a dictionary‐based content analysis to identify which speeches by far‐right members of the European Parliament contain illiberal ideas. Subsequently, we measure the percentage of far‐right illiberal speeches per year. Our study shows that although illiberalism has always been a relevant feature of the far‐right, illiberal ideas have become more prominent in speeches of far‐right members of the European Parliament since 2017, after Brexit and the election of Trump.